APPLICATION OF BREH`S HOLOGRAPHIC GRATINGS CROSSING TYPE FOR REGISTRATION VIBRATION - Тихонов, Є.; Лямець, О.; Давиденко, В.; Пархоцевич, В. (Science-based technologies, 2010)
It is shown that the optical-electronic system in the composition of the volume transmission grating, laser and intermediate sensitive to the vibrations mirror records the vibrations, whose angular amplitude exceed the angular divergence of laser beam. Is represented the mathematical model of this sensor of the vibrations in the form of Taylor series, which describes his response, in particular, the effect of the doubling of the recorded modulation frequency relative to the frequency of acting vibrations.